Kelayakan Darah Palsu (Fake Blood) dari Bunga Rosella Kering (Hibiscus sabdariffa L.) sebagai Alternatif Rias Karakter - Binti Rahmawati; Erna Setyowati (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The use of fake blood in character makeup generally still relies on synthetic materials that have the potential to cause skin irritation; therefore, safer alternatives based on natural ingredients are needed. This study aims to determine the feasibility of fake blood made from dried roselle flowers (Hibiscus sabdariffa L) as an alternative for character makeup, reviewed from aspects of safety and user preference. The research method used was descriptive quantitative, with data collection techniques carried out through clinical tests and preference tests involving respondents using structured assessment instruments.The results showed that all sensory test indicators obtained an average score of 88%, categorized as highly valid. Furthermore, the clinical test results were categorized as safe, with no indications of irritation, allergic reactions, or other skin disorders. In addition, the preference test results showed an average total score of 90%, categorized as highly favorable, indicating that the product is highly feasible in terms of color, texture, and user comfort. Based on these findings, fake blood made from dried roselle flowers (Hibiscus sabdariffa L) is safe and feasible to be used as an alternative in character makeup and has the potential to be developed as a natural-based cosmetic product.